DEVELOPMENT OF EFFECTIVE METHODS OF STRENGTHENING DAMAGED WALLS OF BUILDINGS TO BE RECONSTRUCTED - Mirzababaeva Sakhiba Mirzaakbarovna; Abobakirova Zebuniso Asrorovna; Mirzayeva is the daughter of Zarnigor Alisher; Solijonov is the son of Foziljan Sadiqjan (Journals Park Publishing, 2022)
The article presents defects formed during the operation of buildings and structures, in particular, defects of brick walls and their reinforcement in reconstructed buildings.
Keywords: reconstruction, reinforcement, brick wall, hydrophobic additive, cement mortar, deformation, destruction, foundation